2010
DOI: 10.1016/j.jpainsymman.2009.12.023
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Depression and Pain with Health-Related Quality of Life, Disability, and Health Care Use in Cancer Patients

Abstract: Context Pain and depression are two of the most prevalent and treatable cancer-related symptoms, each present in at least 20-30% of oncology patients. Objectives To determine the associations of pain and depression with health-related quality of life (HRQL), disability, and health care use in cancer patients. Methods The Indiana Cancer Pain and Depression (INCPAD) study is a randomized clinical trial comparing telecare management vs. usual care for patients with cancer-related pain and/or clinically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
3
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(172 citation statements)
references
References 90 publications
8
155
3
6
Order By: Relevance
“…This study also found differences between males and females in their reports of depression that also corresponds with previous studies [3,47]. Kroenke et al found significant difference between male and female regarding the depression in patients with cancer with more symptoms among female patients.…”
Section: Discussionsupporting
confidence: 91%
“…This study also found differences between males and females in their reports of depression that also corresponds with previous studies [3,47]. Kroenke et al found significant difference between male and female regarding the depression in patients with cancer with more symptoms among female patients.…”
Section: Discussionsupporting
confidence: 91%
“…Pain accounted for an additional 21.7% of variance in fatigue; adding pain and depressive symptoms further improved the regression model, increasing the total explained variance to 73.9% (Table 3). Chronic pain and depression are both common symptoms in cancer survivors persisting long after curative treatment [45-47]. Interestingly, co-occurring symptoms can also influence each other and result in a synergistic negative impact on the QoL in cancer survivors [47].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Depression, in particular, has a strong and complex relationship with cancer. 3 Depression has been associated with disease severity, 5 level of patient disability, 6 physical impairment, 7,8 poor performance status [9][10][11] and survival. 12 It is also known that depression is a major source of distress and can have a profound impact on the quality of life (QOL) of breast cancer survivors.…”
mentioning
confidence: 99%